A horseradish peroxidase immobilized radiation grafted polymer matrix: a biocatalytic system for dye waste water treatment. Issue 4 (4th January 2016) - Kumar, Virendra; Misra, Nilanjal; Goel, Narender Kumar; Thakar, Rucha; Gupta, Jagannath; Varshney, Lalit
Abstract : A single step-environment friendly-water based-radiation grafting process was used to fabricate an epoxy functionalized polymer support for one step-covalent immobilization of enzyme HRP in ambient conditions, and tested for dye waste water treatment. Abstract : Horseradish peroxidise (HRP) enzyme, an industrially and environmentally relevant biocatalyst, was covalently immobilized onto epoxy functionalized polypropylene (PP) films, fabricated via 60 Co-gamma radiation induced mutual irradiation grafting of 2, 3-epoxypropyl methacrylate (EPMA) on to PP matrix. The effect of the grafting parameters, such as radiation dose and monomer concentration, on the grafting yield was studied in order to optimize the radiation grafting process. Poly(EPMA)- g -PP films were characterized by grafting yield determination, FTIR, SEM and XPS. The catalytic activity of the immobilized enzyme HRP system was spectrophotometrically assayed using 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) as a substrate. The immobilized HRP system was investigated for repeatability, storage, thermal and pH stability with respect to the free enzyme. The practical applicability of immobilized HRP in the treatment of textile dye waste water was examined by studying the repeated catalytic degradation of Basic Red 29 (BR29) dye. The immobilized enzyme system was found to cause ∼90% degradation of BR29 over a period of 20 days and was observed to be reusable for five cycles without substantial loss in activity.